2007
DOI: 10.1007/s11274-007-9521-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of xylanase production using inexpensive agro-residues by alkalophilic Bacillus subtilis ASH in solid-state fermentation

Abstract: Alkalophilic Bacillus subtilis ASH produced high levels of xylanase using easily available inexpensive agricultural waste residues such as wheat bran, wheat straw, rice husk, sawdust, gram bran, groundnut and maize bran in solid-state fermentation (SSF). Among these, wheat bran was found to be best substrate. Xylanase production was highest after 72 h of incubation at 37°C and at a substrate to moisture ratio of 1:2 (w/v). The inoculum level of 15% resulted in maximum production of xylanase. The enzyme product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 35 publications
10
57
2
Order By: Relevance
“…Similar findings with this study for the optimal initial pH 7 for xylanase production have been reported in previous studies on Bacillus species, including B. pumilus ASH, Bacillus altitudinis DHN8, B. amyloliquefaciens XR44A and B. vallismortis RSPP-15 (Sanghi et al, 2008;Adhyaru et al, 2014;Amore et al, 2013;Gaur et al, 2015). Contrary to this result however, optimal initial pH varied for xylanase production by B. megaterium (pH 7.5), B. subtilis (pH 8) and B. pumilus VLK-1 (pH 6), (Tandon and Sharma, 2014;.…”
Section: Effect Of Initial Ph On Holocellulase Productionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings with this study for the optimal initial pH 7 for xylanase production have been reported in previous studies on Bacillus species, including B. pumilus ASH, Bacillus altitudinis DHN8, B. amyloliquefaciens XR44A and B. vallismortis RSPP-15 (Sanghi et al, 2008;Adhyaru et al, 2014;Amore et al, 2013;Gaur et al, 2015). Contrary to this result however, optimal initial pH varied for xylanase production by B. megaterium (pH 7.5), B. subtilis (pH 8) and B. pumilus VLK-1 (pH 6), (Tandon and Sharma, 2014;.…”
Section: Effect Of Initial Ph On Holocellulase Productionsupporting
confidence: 92%
“…However a sharp decline in xylanase production was recorded thereafter, probably due to proteolysis and enzyme denaturation; while an increase in cellulase activity after an initial decline was observed, which could be attributed to the production of an isoenzyme as have been suggested in literature (Battan et al, 2007;Ritter et al, 2013). Differing from this study however, xylanase production by B. subtilis ASH was initiated at 24 h and attained maximum yield at 72 h (Sanghi et al, 2008). On the other hand, lowest and maximum xylanase production by Gracilibacillus sp.…”
Section: Kinetics Of Growth and Time Course For Xylanase And Cellulascontrasting
confidence: 46%
“…It is produced by bacteria (11,19,37,41), fungi (29,34,41), actinomycetes (33) and yeast (26). Recently, interest in xylanase has markedly increased due its wide variety of biotechnological applications such as pre-bleaching of pulp, improving the digestibility of animal feed stocks, modification of cereal-based stuffs, bioconversion of lignocellulosic material and agro-wastes to fermentable products, clarification of fruit juices and degumming of plant fibers (15,21,44) etc.…”
Section: Introductionmentioning
confidence: 99%
“…The use of cost-effective agroresidues as substrates in solid state fermentation may reduce 468 Sanghi, A. et al Purification and characterization of cellulase-free xylanase the cost of enzyme production substantially (37). Solid state fermentation offers several advantages over submerged fermentation including simplicity of media, greater product yield, easier scale up of process, economy of space, no complex machinery, equipment and control systems etc (2,14).…”
Section: Introductionmentioning
confidence: 99%
“…This result is coherent since lower inoculum density cannot produce enough biomass to produce the biomolecules (Sanghi et al 2008;Selvakumar and Pandey 1999). From the PB12 design, the highest herbicidal activity was obtained when fermentation was carried out at 25°C, moisture content of 50 wt%, 10 wt% of corn steep liquor and soybean bran and 15 wt% of inoculum density.…”
Section: Resultsmentioning
confidence: 99%